IDIOPATHIC THROMBOCYTOPENIC PURPURA AND ORAL SURGERY: case report - Martins, Guilherme; Rozas, Fabrício Gomes; Ribas, Marina de Oliveira; Martins, Wilson Denis (Archives of Oral Research, 2010)
OBJECTIVES: To review the function of platelets in the blood clotting mechanism. To address,conceptualize and classify thrombocytopenic purpura, especially idiopathic thrombocytopenic purpura (ITP),emphasizing the immunological aspects involved in the etiology of the disease. To address the clinicalmanifestations of the disease and the appropriate therapy. To present the case study of a patient with ITPwho requires oral surgical intervention. DISCUSSION: Leukopenia in ITP can be subclinical. The firstmanifestation of the disease can be severe hemorrhaging due to small lacerations or minor medical anddental surgical procedures. The cause of the platelet reduction is idiopathic; an autoimmune reaction in whichthe antibodies destroy the platelets appears to participate in the process. A variety of situations can occur,leading to mild to severe thrombocytopenia. One frequent aspect is the instability of the platelet count,which oscillates inconsistently and may be related to infections and other factors that have not been clearlydetermined, including stress. In the case presented here, the leukopenia in the patient was mild in presentation.However, it was decided that the patient should be referred to a hematologist for preparation and clearance.Oral surgery that compromises the bone, such as exodontia, can present significant difficulties in localizingand clamping intraosseous vessels, which does not only occur in small soft tissue surgeries. CONCLUSIONS:Platelet destruction in ITP occurs from a complex process that is comprised of multiple components of theimmune system. The platelets are prematurely destroyed by antibodies that are aimed at the platelet glycoprotein,which can results in serious, even fatal consequences. It is important to emphasize the significance of themedical history and the appropriate physical examination during the diagnostic process, as well as collaborationwith the patient’s medical clinic. The medical history should compile data such as the beginning of signs andsymptoms, time of development, previous history and types of bleeding, drug intake, and the presence ofother signs and symptoms, such as fever, adenopathy and anemia not only from the patient, but also fromthe family. The most important sign during the physical exam is the presence or report of petechiae occurrence.